The Effect of Live Streaming, Gamification, and Interactive Marketing on Impulse Buying Behaviour of Kahf Products on TikTok with FOMO as a Mediating Variable - Prananta, Putu Resta Wira; Darma, Gede Sri (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine the influence of live streaming engagement, gamification, and interactive marketing on impulse buying behaviour of Kahf skincare products on TikTok, with Fear of Missing Out (FOMO) as a mediating variable. A quantitative approach was employed using purposive sampling, involving 220 Generation Z respondents in Indonesia who had previously made impulsive purchases of Kahf products via TikTok. Data were collected through a questionnaire consisting of 22 indicators and analysed using Structural Equation Modelling–Partial Least Square (SEM-PLS) with the SmartPLS version 4.1.1.2 application. The results indicate that live streaming engagement, gamification, and interactive marketing have a positive and significant effect on impulse buying. These three variables also significantly influence FOMO. Furthermore, FOMO has a positive and significant effect on impulse buying and significantly mediates the influence of gamification and interactive marketing on impulse buying. However, FOMO does not significantly mediate the relationship between live streaming engagement and impulse buying. These findings highlight the importance of participatory, competitive, and emotionally engaging digital strategies in stimulating impulse buying behaviour among Generation Z TikTok users.